Development of canva-based mathematics E-Comics on equivalent fraction material for grade IV elementary school students - Saputro, Hengkang Bara; Arima, Yuni (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
Purpose: This study aims to describe the development procedures and evaluate the quality and feasibility of a mathematics e-comic using a habitual approach to align learning with students' daily routines. Design/methodology/approach: This research follows the Research and Development (R&D) methodology employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects included media, content, instructional, and language experts, alongside classroom teachers and students for pilot testing. Findings: The e-comic was deemed highly feasible based on validation from media (90), content (90), and language (92) experts in the